Communicating risk: variability of interpreting qualitative terms. (21st February 2017) - MacLeod, A.; Pietravalle, S.
Abstract : A survey to examine how verbal expressions of probability and magnitude are interpreted was conducted at an international workshop on plant pest risk analysis. Participants were asked to score words and phrases on a scale of 0 to 100 giving minimum and maximum scores. Using hierarchical clustering, expressions describing probability were categorized into three clusters. One homogeneous cluster describes likely probabilities, a second describes unlikely probabilities and a third heterogeneous group contained words that express great uncertainty rather than committing to describe events as likely or unlikely. Hierarchical clustering was also used to group expressions of magnitude into three broad clusters that basically describe small, medium and large. Qualitative risk assessment protocols that prescribe words to represent probabilities and magnitudes should take into account how widely the words can be interpreted. It is suggested that linking verbal probability terms to specific quantitative probabilities would increase transparency and improve risk communication and risk management decision making.